Hydraulic assessment of a photovoltaic system driving a conventional AC surface electric pump. (June 2021) - Gutierrez, J.; Merino, G.; Lara, D.; Salazar, L.
Abstract: This paper presents a case study of a photovoltaic pumping system for irrigation and/or water storage purposes. To evaluate the efficiency of a photovoltaic water pumping system, hydraulic performance needs to be determined under solar irradiance available. Performance ratio (PR) was used to determine the hydraulic performance of a photovoltaic pumping system, operated by a variable frequency inverter coupled to a conventional alternating current surface pump. For days with solar irradiance above 7.3 peak sun hours (PSH), the system could operate more than 5 h with pressures over 4.7 bar and pump a volume over 45 m 3 of water per day. For days with low solar irradiance, below 3 PSH, the system pumped up to 8 m 3 of water with pressure over 4.1 bar. The results obtained confirm that this kind of PV system is valid option of power for water pumping for irrigation or storage systems. This can benefit small farmers in areas without power grid or those who wish to incorporate photovoltaic energy into an existing conventional pumping system.